Hot Spots of Juvenile Crime: A Longitudinal Study of Arrest Incidents at Street Segments in Seattle, Washington - Weisburd, David (Journal of quantitative criminology, 2009)
Recent studies have shown that crime is concentrated at micro level units of geography defined as hot spots. Despite this growing evidence of the concentration of crime at place, studies to date have dealt primarily with adult crime or have failed to distinguish between adult and juvenile offenses. In this paper, we identify crime incidents in which a juvenile was arrested at street segments in Seattle, Washington, over a 14-year period, to assess the extent to which officially recorded juvenile crime is concentrated at hot spots. Using group-based trajectory analysis, we also assess the stability and variability of crime at street segments over the period of the study. Our findings suggest that officially recorded juvenile crime is strongly concentrated. Indeed, just 86 street segments in Seattle include one-third of crime incidents in which a juvenile was arrested during the study period. While we do observe variability over time in trajectories identified in the study, we also find that high rate juvenile crime street segments remain relatively stable across the 14 years examined. Finally, confirming the importance of routine activity theory in understanding the concentration of juvenile crime in hot spots, we find a strong connection between high rate trajectory groups and places likely to be a part of juvenile activity spaces. Though place-based crime prevention has not been a major focus of delinquency prevention, our work suggests that it may be an area with great promise.